Sistem Penyimpanan Arsip di Kantor Camat Koto XI Tarusan Pesisir Selatan - Hafizh, Muhammad; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Writing this paper aims to describe: 1) Archive storage facilities, 2) Archive storage system, 3) obstacles and efforts in archive storage system in Koto XI Sub-Bereau Head Office of South Pesisir. The method used is descriptive method. Data collected through abservation and interview. The observation was done directly at Koto XI Sub-Bereau Head Office of South Pesisir.Based on the result of these studies can be summarized as follows. First, the archive storage facility in the Offcie of the Sub-DistrictÂ  Head Koto XI South Coast using archival storage boxes and filing cabinets. Secondly, the archive storage system at the South Coast Koto XI Sub-Dictrict Head Office uses an alphabetical storage system and uses chronological and systematic problems and storage systems or dates. Third, the obstacles and efforts encountered in the implementation of achival storage is less precise storage space, lack of professionals and archivists archive professionals in the Office of the Koto XI Sub-District Head South Coast Pusan.Keyword : archive, filling system, means of archiving, Filing system.